APTT Revisited: Detecting Dysfunction in the Hemostatic System Through Waveform Analysis - Toh, Cheng Hock (Thrombosis and Haemostasis, 1999)
Despite extensive investigations in both experimental and clinical disseminated intravascular coagulation (DIC), much remains to be learned about this condition of hemostatic dysfunction. Although the technological armory available to the clinical investigator has expanded enormously since the early 1980s, particularly with regard to immunologically-based testing, the sobering fact is that prognosis has remained dismally unchanged.1 Although some of the new laboratory approaches can identify DIC at an early enough stage to allow for useful clinical intervention, most require a level of stringency in performance that is not attainable in the routine clinical setting.2 The pace of acute DIC precludes many of these specific tests, and reliance is still based on traditional screening assays, such as the prothrombin time (PT), activated partial thromboplastin time (APTT) and platelet count (Plt). These tests lack specificity on an individual basis and are only useful in DIC if there is further determination of fibrinogen (Fgn) and fibrin breakdown products (fdp)/D-Dimers.3 However, changes in these battery of tests seldom occur together. As a result, the realization of DIC is often only made after serial testing, with the inevitable delay and consequent jeopardization of patient critical care.4 The numerous failures of new therapies in sepsis and DIC testifies to this problem of a lack of early definition in the disease process to forewarn the clinician of more timely intervention.5 The gold standard must, therefore, be a single, rather than multiple, assay system that is both sensitive and specific for early DIC and simple and rapid to perform. It is therefore, not too surprising that such a test has remained elusive for such a considerable length of time.In the context of complex scenarios, the simplest of approaches can often be the most rewarding. Such an axiom could fit with the description of APTT transmittance waveform analysis as a useful test in DIC that could also potentially lead to an improved understanding of the condition.